Strategi Hidup Bersahabat dengan Alam oleh Anak Sekolah Minggu GKPPD Ressort Suak Kelasen - Flesia Nanda Uli Boangmanalu; Andika Mason Alay Padang; Eli Boi Sinamo; Heppi Manik; Siska Tumangger (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
This article is based on the fact that children still don't care about the environment and nature. Children tend to feel trivial about their actions in littering. Without realizing it, it can damage nature and bring disaster to the area where you live. The aim of this research is to provide and obtain strategies that can be used by GKPPD Ressort Suak Classen Sunday school children to protect and care for nature. The method used is descriptive qualitative, namely analyzing, comparing and concluding various opinions from source books/journals and interviews from various experts and figures regarding strategies that are easy for Sunday school children to apply in protecting and being friendly with nature. Children who truly understand the importance of nature for human life will have a caring attitude towards the environment and help the next generation to experience the pleasures of nature in good condition.